Quantifying the paradoxical effect of higher systolic blood pressure on mortality in chronic heart failure. Issue 1 (24th July 2008) - Raphael, C E; Whinnett, Z I; Davies, J E; Fontana, M; Ferenczi, E A; Manisty, C H; Mayet, J; Francis, D P
Abstract : Background: Although higher blood pressures are generally recognised to be an adverse prognostic marker in risk assessment of cardiology patients, its relationship to risk in chronic heart failure (CHF) may be different. Objective: To examine systematically published reports on the relationship between blood pressure and mortality in CHF. Methods: Medline and Embase were used to identify studies that gave a hazard or relative risk ratio for systolic blood pressure in a stable population with CHF. Included studies were analysed to obtain a unified hazard ratio and quantify the degree of confidence. Results: 10 studies met the inclusion criteria, giving a total population of 8088, with 29 222 person-years of follow-up. All studies showed that a higher systolic blood pressure (SBP) was a favourable prognostic marker in CHF, in contrast to the general population where it is an indicator of poorer prognosis. The decrease in mortality rates associated with a 10 mm Hg higher SBP was 13.0% (95% CI 10.6% to 15.4%) in the heart failure population. This was not related to aetiology, ACE inhibitor or β blocker use. Conclusion: SBP is an easily measured, continuous variable that has a remarkably consistent relationship with mortality within the CHF population. The potential of this simple variable in outpatient assessment of patients with CHF should not be neglected. One possible application of this information is in the optimisation of cardiac resynchronisation devices.